Wind-induced vibration control of tall TV towers using a part of the main structure as a vibration absorber substructure - Nahmat Khidaie (Iranian Society of Structrual Engineering (ISSE), 2019)
The present paper proposes a new control strategy to mitigate wind-induced vibrations of tall TV towers. Based on the proposed idea, a part of the main structure of the tower is isolated and regarded as a dynamic vibration absorber. In order to investigate the effectiveness of the proposed system, the 310-m tall Nanjing TV tower in China, which has two observation decks at the heights 180 m and 240 m, is studied. The wind-induced responses are obtained for the following cases: uncontrolled structure; controlled structure equipped with the TMD system; and the controlled structure with an isolated substructure at the upper observation deck level. The structure is modelled as a multi-degree-of-freedom (MDOF) lumped mass vertical cantilever beam. The TMD system and the isolated substructure are modelled as a lumped mass connected to the upper observation deck by a parallel stiffness and damper system. All the calculation works related to the frequency-domain analysis, optimizing the system, simulating the wind velocity, and the time-domain analysis are carried out using the MATLAB software. The results indicate that the proposed self-control structural system has higher vibration control capacity than the TMD system. The proposed system can effectively reduce the acceleration response of the structure and improve occupant comfort during critical wind speed. In the proposed system, since a part of the main structure performs as a vibration absorber, it is not required to assign a valuable space of the observation deck for the installation of an additional mass damper and the corresponding clearance to accommodate its large strokes.